Sidelobe Suppression with Null Steering by Independent Weight Control. (10th June 2015) - Khan, Zafar-Ullah; Malik, Aqdas Naveed; Zaman, Fawad; Hussain, Syed Azmat; Khan, Abdul-Rehman
Abstract : A uniform linear array of n antenna elements can steer up to n - 1 nulls. In situations where less than n - 1 nulls are required to be steered, the existing algorithms have no criterion to utilize the remaining weights for sidelobe suppression. This work combines sidelobe suppression capability with null steering by independent weight control. For this purpose, the array factor is transformed as the product of two polynomials. One of the polynomials is used for null steering by independent weight control, while the second one is for sidelobe suppression whose coefficients or weights are determined by using convex optimization. Finally, a new structure is proposed to incorporate the product of two polynomials such that sidelobe suppression weights are decoupled from those of null steering weights. Simulation results validate the effectiveness of the proposed scheme.